The need to reform mental health legislation in Commonwealth countries. Issue 1 (February 2014) - Pathare, Soumitra; Shields, Laura; Sagade, Jaya; Nardodkar, Renuka
Abstract : The United Nations Convention on the Rights of Persons with Disabilities (CRPD) serves as a comprehensive and legally binding framework for the rights of persons with mental illness. The extent to which countries have adapted their mental health legislation to reflect the binding provisions outlined in the CRPD is unclear. This paper reviews the situation across the Commonwealth.